Letter of Collaborative Agreement between the International Livestock Research Institute (ILRI) and the Institute of Geophysics, Space Science and Astronomy (IGSSA), Addis Ababa University - International Livestock Research Institute; Addis Ababa University (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Letter of Collaborative Agreement between the International Livestock Research Institute (ILRI) and the Institute of Geophysics, Space Science and Astronomy (IGSSA), Addis Ababa University.